IMPLEMENTATION INTERACTIVE AND COLLABORATIVE ONLINE LEARNING ENGLISH FOR FOREIGN LANGUAGE MOODLE-BASED - Rizky Eka Prasetya; Anindya Putri Pradipta; Geri Suratno (ETERNAL (English, Teaching, Learning and Research Journal), 2022)
Moodle virtual learning transformed the implementation of online English education. This Learning Management System (LMS) was the most accepted in Higher Education in Indonesia. The qualitative study investigates and determines the integration of Moodle features on interactive and collaborative English teaching approaches. Case studies practice various qualitative research approaches for 43 language lecturers as the respondent. Illustrative case studies assisted essentially in obtaining the unknown common and providing pedagogical members with a specific language regarding the subject in the problem. The result exposed the opportunity to implement an interactive and collaborative teaching approach in the English language educational process. The availability of Moodle features is concerned with the activities and resources main feature in Moodle. The interactive Moodle feature involved assignments, lessons, quizzes, and surveys. English language learners who engage in interactive online learning experiences are compelled to participate in their education. Involving them in the English language online education process is critical to their achievement. In the meantime, Collaborative Moodle features involved chat, forum, glossary, and wiki. These fundamental features were revealed to help English lecturers establish the learner-centered English pedagogy mode as course designers. Integrating collaborative activities into online courses improves performance outcomes for English language learners. The Moodle virtual English online pedagogy would be the proper system to accommodate and facilitate education in Higher Education. English lecturers as course designers and instructors needed to be aware of the improvement of virtual media and made enhancement English language learners